An Empirical Method for Particle Damping Design - Zhi Wei Xu; K.W. Chan; W.H. Liao (Shock and Vibration, 2004)
Particle damping is an effective vibration suppression method. The purpose of this paper is to develop an empirical method for particle damping design based on extensive experiments on three structural objects – steel beam, bond arm and bond head stand. The relationships among several key parameters of structure/particles are obtained. Then the procedures with the use of particle damping are proposed to provide guidelines for practical applications. It is believed that the results presented in this paper would be helpful to effectively implement the particle damping for various structural systems for the purpose of vibration suppression.